Final Report of the United Nations Commission of Experts Established Pursuant to Security Council Resolution 780 (1992), 27 May 1994 - International Human Rights Law Institute
The series contains 28 volumes of the 'Final Report of the United Nations Commission of Experts' including twelve Annexes. The final result of the Commission's 18 months of investigative work consists of five parts: I. Mandate, Structure and Methods of Work; II. Applicable Law; III. General Studies; IV. Substantive Findings; and V. General Conclusions and Recommendations.